Giving Motivation to Students at SDN 1 Purwoharjo Banyuwangi in 2022 - Edi Irwanto; Mislan; Moh. Agung Setiabudi; Lutfi Irawan Rahmat; Dadang Mubin (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2023)
Banyuwangi Ayo Mengajar (BAM) is an activity that involves all groups to be involved in the world of education, and invites people from various professions to join as volunteers and go to schools to motivate students. This activity aims to provide students with an understanding of various knowledge that comes from someone who has abilities in their respective fields. The method used is the lecture method. This activity was held on October 18 2022 at SDN 1 Purwoharjo. The results of this activity were that the students of SDN 1 Purwoharjo had goals they wanted to achieve, including 14 students from the TNI or Polri, and 12 educators. doctor 7 students. health workers as many as 4 students. become self-employed as many as 3 students. The reason they have these ideals is based on their family (parent and sibling professions) and the surrounding environment (neighboring professions). Understanding is also given to add insight to students and how to achieve these goals.